2018
DOI: 10.1158/0008-5472.can-18-0234
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Stromal p38MAPK/MK2 Pathway Limits Breast Cancer Metastases and Chemotherapy-Induced Bone Loss

Abstract: The role of the stromal compartment in tumor progression is best illustrated in breast cancer bone metastases, where the stromal compartment supports tumor growth, albeit through poorly defined mechanisms. p38MAPKα is frequently expressed in tumor cells and surrounding stromal cells, and its expression levels correlate with poor prognosis. This observation led us to investigate whether inhibition of p38MAPKα could reduce breast cancer metastases in a clinically relevant model. Orally administered, small-molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 52 publications
(83 reference statements)
2
34
0
Order By: Relevance
“…Data in mice have shown that MK2 does contribute to tumor progression by promoting M2 macrophage polarization and tumor angiogenesis which in turns promotes tissue renovation that governs cell invasion and metastasis [31]. Furthermore, inhibition of the stromal p38MAPK/MK2 pathway was found to limit breast cancer metastases in mice [32]. These data from others along with our data showing the striking classification of metastasis status among gastric cancer patients by MK2 and its association with a wide range of cytokines suggests pathway blockade is promising for immunotherapy treatment [33].…”
Section: Discussionmentioning
confidence: 99%
“…Data in mice have shown that MK2 does contribute to tumor progression by promoting M2 macrophage polarization and tumor angiogenesis which in turns promotes tissue renovation that governs cell invasion and metastasis [31]. Furthermore, inhibition of the stromal p38MAPK/MK2 pathway was found to limit breast cancer metastases in mice [32]. These data from others along with our data showing the striking classification of metastasis status among gastric cancer patients by MK2 and its association with a wide range of cytokines suggests pathway blockade is promising for immunotherapy treatment [33].…”
Section: Discussionmentioning
confidence: 99%
“…We chose an ATI450 concentration of 1000 ppm for our preclinical mouse studies. This is lower than the maximum dose employed while still within the range of maximum MK2 pathway inhibition; furthermore, this concentration has been effective in previous publications [32,33].…”
Section: Ati450 Dosing Studiesmentioning
confidence: 78%
“…Senescent cells generated by genotoxic stress contributes to various toxicities, including tumor promotion and relapse, via secretion of various pro-inflammatory NASP factors [5][6][7] . Interestingly, exposure of MCF7 (breast cancer), A549 and HCC827 (lung cancer) cells to the CM of abemaciclib-induced senescent cells had a strongly reduced pro-proliferative effect in comparison to CM from doxorubicin-induced senescent cells (Extended data Fig.…”
Section: Abemaciclib Treatment Exerts Minimal Toxicitymentioning
confidence: 99%
“…Senescence induction acts as a potent tumor suppressive mechanism by restraining cancer cell proliferation and activating tumor immunosurveillance 4 . However, increasing evidence suggests that therapy-induced normal cells promote chronic inflammation and several shortand long-term adverse effects, including fatigue, myelosuppression, cardiomyopathy, bone loss, cancer progression and relapse, and that their genetic and pharmacological removal is sufficient to improve healthspan [5][6][7][8] . These senescence-associated detrimental effects are mainly mediated by pro-inflammatory SASP cytokines and chemokines, which are normally elevated in cancer patients suffering from a variety of adverse reactions to cancer therapies 9,10 .…”
Section: Introductionmentioning
confidence: 99%